Асимптотичні m-фазові солітоноподібні розв'язки сингулярно збуреного рівняння Кортевега - де Фріза зі змінними коефіцієнтами. II - Самойленко, В.Г.; Самойленко, Юл.І. (Український математичний журнал, 2012)
Рассматривается задача о построении старших членов асимптотического многофазового солитоноподобного решения сингулярно возмущенного уравнения Кортевега – де Фриза с переменными коэффициентами. Установлена оценка, с которой построенное асимптотическое решение удовлетворяет исходному уравнению. We consider the problem of the construction of higher terms of asymptotic many-phase soliton-type solutions of a singularly perturbed Korteweg–de Vries equation with variable coefficients and determine the accuracy with which the obtained asymptotic solution satisfies the original equation.